IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY DALAM MENINGKATKAN KEPUASAN PELANGGAN - Ulaika, Ega Rohma Nur; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The qualitative method has been applied in this research as the research method. The qualitative method which has been applied by the researcher is not to prove a hypothesis, yet it is to find out and to analyze the implementation of CSR on PT A.J. Central Asia Raya Surabaya.It has been found form the result of the research that the company has implemented the CSR in the form of blood donation, planting 1000 trees, scholarships, reward giving or souvenirs to employees and customers. The implementation of the CSR has an impact on the employeesâ satisfaction in which it has made the employees feel comfortable in working so the employees become more loyal to the company. Meanwhile, the impact on the customer is the emergence of feeling cared, so they have become loyal customer. It can be proven by the increasing number of customer and the premium income by 11% in 2013.It is expected from the discussion above that the company can maintain the CSR program, add the CSR program with the new one, and can improve the service quality to its customer from the communication aspect.Keywords: corporate social responsibility, customer satisfaction, employee satisfaction, premium income